Platelet Internalization Mediates Ferroptosis in Myocardial Infarction. Issue 2 (10th November 2022) - Miao, Shuo; Zhang, Qingsong; Ding, Wei; Hou, Bo; Su, Zhe; Li, Mengyang; Yang, Lanting; Zhang, Jun; Chang, Wenguang; Wang, Jianxun
Abstract : Background: Myocardial cell death is the hallmark of myocardial infarction. In the process of myocardial injury, platelets contribute to the pathogenesis by triggering intense inflammatory responses. Yet, it is still unclear if platelets regulate cardiomyocyte death directly, thereby exacerbating myocardial injury in myocardial infarction. Methods: We describe a mechanism underlying the correlative association between platelets accumulation and myocardial cell death by using myocardial infarction mouse model and patient specimens. Results: Myocardial infarction induces platelets internalization, resulting in the release of miR-223-3p, a platelet-enriched miRNA. By targeting the ACSL3, miR-223-3p delivered by internalized platelets cause the reduction of stearic acid-phosphatidylcholine in cardiomyocytes. The presence of stearic acid-phosphatidylcholine protects cardiomyocytes against ferroptosis. Conclusions: Our work reveals a novel mechanism of platelet-mediated myocardial injury, highlighting antiplatelet therapies could potentially represent a multimechanism treatment of myocardial infarction, and implying ferroptosis being considered as novel target for therapeutics.